Life Cycle Cost of Eco-Friendly Building Materials in Office Buildings: Supporting GBCI Greenship Certification - Asep Suhana; Hetty Fadriani; Handoko Subawi (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Indonesia’s construction sector faces challenges in reducing environmental impacts while maintaining the economic feasibility of projects. Objective: This study aims to analyze the life cycle cost (LCC) of environmentally friendly materials used in office building envelope components and evaluate their contribution to achieving points in the Green Building Council Indonesia (GBCI) Greenship certification system. Methods: A quantitative comparative case study approach was employed on a five-story office building in Jakarta, with an analysis period of 30 years and a discount rate of 8%. The evaluated components included wall systems, concrete structures, and façade glazing, comparing conventional materials with environmentally friendly alternatives such as autoclaved aerated concrete (AAC) blocks, geopolymer concrete, and low-emissivity (low-e) glass. The data were analyzed using the LCC equation and supplemented with sensitivity analyses of discount rates and energy price variations. Results: The results showed that although the initial costs of environmentally friendly materials were 12–18% higher, the total LCC over 30 years was 9.5–9.8% lower than that of conventional materials. The cost break-even point occurred between the 9th and 11th years. Furthermore, the application of these materials contributed six points to the Material Resources and Cycle category in the GBCI Greenship v1.2 rating system. Conclusion: This study concludes that the LCC approach can serve as a basis for rational decision-making to encourage the adoption of green building materials in Indonesia.